Being a Parent in the Field: Implications and Challenges of Accompanied Fieldwork - Haug, Michaela; Stolz, Rosalie; Braukmann, Fabienne; Metzmacher, Katja (transcript, 2020)
How does being a parent in the field influence a researcher's positionality and the production of ethnographic knowledge?Based on regionally and thematically diverse cases, this collection explores methodological, theoretical, and ethical dimensions of accompanied fieldwork. The authors show how multiple familial relations and the presence of their children, partners, or other family members impact the immersion into the field and the construction of its boundaries.Female and male authors from various career stages exemplify different research conditions, financial constraints, and family-career challenges which are decisive for academic success.